ANALISIS PENERAPAN PSAK No. 102 TENTANG AKUNTANSI MURABAHAH (Studi Kasus Pada Lembaga Keuangan Mikro Syariah Baitul Qiradh Afdhal Cabang Kota Lhokseumawe) - Amrullah, Amrullah; Arfan, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study is aimed to analyze the application of PSAK No. 102 about murabaha accounting system on shariah microfinance institutions Baitul Qiradh Afdal Lhokseumawe Regional. Thisstudy uses descriptive analyses method. The data used is primary data obtained directly by interview , and secondary data through documentation and study of literature.The results showed that the application of the murabaha accounting system on shariah microfinance institutions Baitul Qiradh Afdal Lhokseumawe Regional with PSAK No. 102 about murabaha accounting has not been fully run in accordance with the applicable rules.KeywordsMurabahah, PSAK No. 102, Baitul Qiradh